2013
DOI: 10.1080/03601234.2013.824224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triazole pesticide formulation on bovine culture cells

Abstract: To date, most data about the possible genotoxic effect of triazole pesticides are focused on laboratory animals resulting in limited information on further non-target organisms such as cattle. The objective of the present study was to investigate the effect of triazole (tebuconazole/prothioconazole) fungicide formulation on the induction of chromosomal aberrations (CAs), sister chromatid exchanges (SCEs) and DNA fragmentation in bovine cultured lymphocytes. Our results showed that the fungicide formulation did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Based on this, we assume that epoxiconazole can reduce the number of spermatids and germ cells and result in abnormalities of germ cell development. There is no physiological germ cell apoptosis to maintain the male germline during germ cell development [36,37]. Therefore we focused on the number of meiotic cells in the adult male nematode and the meiosis entering time to illustrate germ cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we assume that epoxiconazole can reduce the number of spermatids and germ cells and result in abnormalities of germ cell development. There is no physiological germ cell apoptosis to maintain the male germline during germ cell development [36,37]. Therefore we focused on the number of meiotic cells in the adult male nematode and the meiosis entering time to illustrate germ cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer inclusion membranes were prepared as reported in the earlier paper [ 34 , 35 , 36 , 37 , 40 , 45 ]. The membrane contained 2.7 cm 3 o-NPPE/1 g CTA, and 0.5–1.5 mol/dm 3 of 1-alkyltriazole 1 – 9 ( Table 1 ) based on a plasticizer.…”
Section: Methodsmentioning
confidence: 99%
“…Transport experiments were carried out in the system described in earlier papers [34][35][36][37]40,45] at 20 ± 0.2 • C. The feed phase was an aqueous solution of metal ions with a concentration of C 0,M = 0.001 mol/dm 3 each. The feed phase pH was kept constant (pH = 4.0).…”
Section: Transport Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and co-workers [9] have observed that exposure to TB can alter thyroid hormone levels as well as gene transcription in zebrafish larvae. The results obtained by Holečková et al [10] indicated that TB can exert either cytotoxic and/or genotoxic effect on bovine peripheral lymphocytes. TB has been also found in farm workers with maximum concentrations of 19.2 μg/L and 2.22 ng/kg in urine and hair samples, respectively [11,12].…”
Section: Introductionmentioning
confidence: 99%